Successful Treatment of Multiple Arterial Thrombosis in Premature Infant: Clinical Case - Ekaterina S. Matros; Anton O. Aksenov; Sofia A. Demina; Liubov E. Larina (Педиатрическая фармакология, 2024)
Background. Neonatal thrombosis remains a complex and urgent challenge due to the presence of certain features of the hemostasis system in newborns and the variety of clinical signs. Management approaches are still under consideration, therapeutic experience of thrombolytic therapy (TLT) remains limited and requires benefit-risk assessment. Clinical case description. Clinical case of premature infant with multiple arterial thrombosis diagnosed on the 1st day of life is presented. Modern diagnostic features have allowed to establish the right diagnosis quickly and to start the treatment in time despite the similarities of clinical signs with congenital heart disease. Conclusion. TLT and heparin therapy have saved the child’s life, reversed ischemia, and preserved lower limbs from death. Doctors must perform dynamic monitoring during TLT to diagnose and correct hemorrhagic complications in timely manner.